Phytochemical Characterization of Water Avens (Geum rivale L.) Extracts: Structure Assignment and Biological Activity of the Major Phenolic Constituents - Anastasia Orlova; Elana Kysil; Elena Tsvetkova; Darya Meshalkina; Andrei Whaley; Anastasiia O. Whaley; Annegret Laub; Antonio Francioso; Olga Babich; Ludger A. Wessjohann; Luciana Mosca; Andrej Frolov; et al. (Plants, 2022)
Water avens (Geum rivale L.) is a common Rosaceae plant widely spread in Europe and North America. It is rich in biologically active natural products, some of which are promising as prospective pharmaceuticals. The extracts of water avens are well known for their triterpenoid metabolites and associated anti-inflammatory, antimicrobial and antioxidant activities. However, the polyphenolic profiles of G. rivale L. are still awaiting complete characterization. Accordingly, the contribution of its individual components to the antioxidant, antibacterial and neuroprotective activity of the extracts is still unknown. As this plant can be available on an industrial scale, a better knowledge of its properly-relevant constituents might give access to new highly-efficient pharmaceutical substances and functional products. Therefore, herein we comprehensively characterize the secondary metabolome of G. rivale by ESI-HR-MS, ESI-HR-MSn and NMR spectroscopy with a special emphasis on the polyphenolic composition of its aerial parts. Furthermore, a multilateral evaluation of the antioxidant, neuroprotective and antibacterial properties of the aqueous and ethyl acetate fractions of the total aqueous alcoholic extract as well as individual isolated polyphenols was accomplished. Altogether four phenolic acid derivatives (trigalloyl hexose, caffeoyl-hexoside malate, ellagic acid and ellagic acid pentoside), six flavonoids (three quercetin derivatives, kaempferol and three its derivatives and two isorhamnetin derivatives) and four tannins (HHDP-hexoside, proantocyanidin dimer, pedunculagin I and galloyl-bis-HHDP-hexose) were identified in this plant for the first time. The obtained aqueous and ethyl acetate fractions of the total extract as well as the isolated individual compounds showed pronounced antioxidant activity. In addition, a pronounced antibacterial activity against several strains was proved for the studied fractions (for ethyl acetate fraction the highest activity against E. coli АТСС 25922 and S. aureus strains ATCC 27853 and SG-511 (MIC 15.6 μg/mL) was observed; for aqueous fraction—against Staphylococcus aureus SG-511 (MIC 31.2 μg/mL)). However, the anti-neurodegenerative (neuroprotective) properties could not be found with the employed methods. However, the antibacterial activity of the fractions could not be associated with any of the isolated individual major phenolics (excepting 3-O-methylellagic acid). Thus, the aerial parts of water avens represent a promising source of polyphenolic compounds with antioxidant activity and therefrom derived human health benefits, although the single constituents isolated so far lack a dominant selectively bioactive constituent in the bioassays performed.